Novel Associations Between Interleukin-15 Polymorphisms and Post-training Changes of Body Composition Parameters in Young Nonobese Women - Ficek, Krzysztof; Ciȩszczyk, Paweł; Leźnicka, Katarzyna; Kaczmarczyk, Mariusz; Leońska-Duniec, Agata (Frontiers in Physiology, 2019)
Based on the important role of interleukin-15 (IL-15) in human metabolism and, in consequence, in body composition modulation, we examined whether rs1589241 and rs1057972 polymorphisms, analyzed individually or in combination, would influence the effects of a training program. Accordingly, we studied the allele and genotype distribution in a group of 163 young nonobese Caucasian women measured for selected body mass and composition, as well as biochemical parameters before and after the completion of a 12-week endurance training program. After a week-long familiarization stage, low-high impact aerobics were conducted three times a week for 60 min, at an increasing intensity from about 50 to 80% of HRmax. With reference to rs1057972 genotypes, there were two significant genotype × training interactions, in which (i) fat mass percentage (FM%) significantly decreased among the AA homozygotes (p = 0.00002) and AT heterozygotes (p = 0.00002), and (ii) fat free mass (FFM) increased only among the AT heterozygotes (p = 0.0003), whereas in the AA homozygotes there was only a borderline significance (p = 0.065). No genotype × training interactions were found for the second rs1589241 polymorphism. Moreover, the carriers of the[T;A] haplotype (when compared with reference haplotype) displayed significant decrease in FM% (p = 0.027) and increase in FFM (p = 0.014) in response to the applied training program. Our data highlight novel associations between specific IL-15 genotype and different post-training changes of FM% and FFM parameters. The results suggest that harboring the rs1057972 A allele and/or the [T;A] haplotype is favorable for achieving specific positive training-induced body composition changes.